Kedudukan Sinamot Sebagai Syarat Sahnya Perkawinan Dalam Masyarakat Adat Batak Toba Menurut Perspektif Hukum Positif - Panjaitan, Wijaya Natalia; Pratiwi, Dita Ayudia; Nabila, Syadzwina Hindun (BAMETI Customary Law Review, 2024)
Customary law is a law that is applied and evolve in the life of the community which is constitutionally equal to the law in general. One of them is the validity of Batak toba customary law for the Batak toba indigenous people. Batak toba culture has a custom called giving Sinamot to the woman as a token when carrying out traditional marriage as a symbol of the seriousness of marriage. The sinamot requirement in traditional Batak marriage is a mandatory requirement in marrying, but oftentimes this sinamot customary event is only considered as a traditional and cultural ceremonial event that is held and not as a customary requirement as a legal provision that should be recognised as equal to positive law provisions that have legal implications. This research is to identify the position of sinamot as a condition for the validity of Batak toba traditional marriage from the perspective of positive law. The research method is normative juridical research with a literature review. Sinamot is not only a customary and cultural event requirement in the implementation of marriage but also a customary requirement that has the same value as legal provisions as one of the conditions for the validity of marriage in addition to the validity based on Marriage Law Number 1 of 1997 Juncto Law Number 16 of 2019.